The Dynamics of Development and Leadership of Muhammadiyah in Bantaeng: A Local Historical Study, 1927–2020 - Ananda Utami; Amirullah (Smart: Journal of Global Islamic Studies and Social Science, 2026)
The Muhammadiyah movement first entered Bantaeng Regency in 1927, initiated by three merchants: Ambo Paria, Tanawali, and Mahmud Usman. Officially recognized as a branch in August 1928, it advanced to branch status in 1939 and became a Regional Leadership (Pimpinan Daerah) in 1967. Leadership dynamics and organizational development endured Japanese and Dutch colonial pressures, yet post-independence efforts saw the establishment of 21 sub-branches across five districts. Core activities revolved around tajdid preaching, rejection of bidʻah practices, and educational charitable endeavors. From 1939 through the early twenty-first century, Muhammadiyah Bantaeng founded various institutions: mu’allimin madrasas, a Neutral Dutch School (NHS), junior and senior madrasahs (MTs, MA), pesantrens, kindergartens, and primary schools, integrating modern curricula with Islamic values. This trajectory underscores Muhammadiyah’s strategic role in socio-religious transformation and human capital enhancement in Bantaeng. This study provides a local historical chronicle of organizational evolution, preaching strategies, and educational contributions from 1927 to 2020.